The effectiveness of health promotion using social media on adolescent knowledge about Covid-19 in the work area of Health Center Batu Panjang, Rupat District, Bengkalis Regency - Nanda Tri Cahtiya; Hastuti Marlina; Novita Rany (Institute of Computer Science (IOCS), 2022)
Health promotion through teen social media can increase knowledge about Covid-19 by 95% and influence behavior to prevent Covid-19 by 77%. The aim of this study was to determine the effectiveness of the use of social media for health promotion on youth Covid-19 knowledge in the workplace at Batu Panjang Health Centre, Rupat District, Bengalis Regency in 2021. This type of research is quantitative analysis with a quasi-experimental design. The population for this study was all 12th graders at Rupat High School, for a total of 30 respondents. Research tools are using Whatsapp and Instagram to promote health. Collecting data using a questionnaire via google form. Data analysis used univariate and bivariate tests. The result of the research is that there is a difference in the average value of respondents' knowledge before and after health promotion using whatsapp and instagram is 63.73 and 85.33 in the whatsapp group and 64.13 and 80.00 in the instagram group. The results of the paired-samples T test (dependent T test) showed that health promotion was effective regarding Covid-19 using social media WhatsApp and Instagram to increase respondents' knowledge about COVID-19 in the Batu Panjang Public Health Center, Rupat District, Bengkalis Regency. It is recommended to the puskesmas and schools to partner in the implementation of school children's services by using social media so that the prevention of covid-19 is maximized.